Study on the change and acculturation of dietary pattern of Southeast Asian workers living in South Korea. (1st October 2017) - Lee, Eun Jung; Lee, Kyung-Ran; Lee, Seung-Joo
Abstract: This study analyzed the dietary pattern of Southeast Asian workers (Vietnamese, Thais, Cambodians and Myanmar) living in South Korea in order to recognize the dietary changes after they moved to South Korea. Questionnaires were completed by 251 Southeast Asian workers living in South Korea. Using a self-administered questionnaire, we assessed the diets before and after living in the hometown and in South Korea. Significant changes observed in the Southeast Asian workers were decreased in consumption frequency of fresh fruits, cooked vegetables, rice noodles, green tea and glutinous rice, and increase in consumption of Kimchi, seaweed, milk, coffee and pizza. These changes were attributed to rapid dietary acculturation. The frequencies of eating homemade food were significantly decreased after they came to Korea except for Thais. Thais showed the highest frequencies of eating homemade food daily among others. 28.2% of respondents said their health condition had deteriorated after living in South Korea due to difficulties to adapt Korean food, increased frequencies of eating instant food, and lacking exercises. By providing understanding of the dietary patterns of Southeast Asian workers, these results can be used for preliminary data to develop a program for their Korean food adaptation.